Comparative analysis of the functional status of hip joints before total hip replacement in patients with ankylosing spondylitis, rheumatoid arthritis and coxarthrosis: preliminary data of a retrospective study - A. O. Dubinin; A. E. Khramov; T. V. Dubinina; E. V. Ilinykh; E. I. Byalik (Научно-практическая ревматология, 2025)
Approximately 2.7% of all total joint arthroplasties are performed on patients with inflammatory arthritis. Severe structural and functional changes of the hip joints (HJ) increase the risks of intra- and postoperative complications.The aim of the study – to carry out a comparative analysis of the functional state of the hip joints before total hip arthroplasty (THA) in patients with ankylosing spondylitis (AS), rheumatoid arthritis (RA) and osteoarthritis (OA).Materials and methods. A retrospective study included 170 patients diagnosed with AS who met the modified 1984 New York criteria. For comparative analysis, age-matched individuals with AS were selected from the cohort of RA (n=1604) and OA (n=1458) patients. The preliminary analysis included data on 68 patients with RA and 52 with secondary coxarthrosis (posttraumatic and due to HJ dysplasia). All patients underwent elective THA between 1998 and 2020. Among AS patients, men (80.6%) predominated. The mean age was 38.1±11.3 years, duration of disease from the onset of the first symptoms was 17.0±8.5 years, duration of HJ pain before THA was 7.4±4.8 years. The majority of patients with RA were women (83.8%). The mean age of the patients was 42.8±9.9 years. The mean duration of RA from disease onset to THA HJ was 15.9±8.6 years. The duration of HJ pain before surgical treatment was significantly (p<0.05) less than in AS – 5.7±2.3 years. Women (57.7%) were also predominant among patients with OA. Patients with OA at the time of THA HJ were significantly older than AS patients, their mean age was 45.3±8.4 years. The duration of pain in HJ was 6.8±5.3 years. Preoperative functional state of HJ was determined using the modified Harris scale.Results and discussion. The mean total Harris scale score before surgical treatment in AS was significantly higher than in RA and lower than in OA: 38.0±15.4, 33.9±12.7, and 44.9±12.2, respectively. In most parameters of the Harris scale, patients with AS had similar indicators with RA patients. The following parameters of the Harris scale were significantly more frequently used in RA and were worse in comparison with AS: fixed adduction, fixed inward rotation, fixed flexion contracture, HJ flexion. Patients with AS were significantly more likely than those with OA to have more severe claudication, problems with distance walking, more frequent use of additional support, and more severe anatomical deformities on the Harris scale.Conclusion. Assessment of function according to the Harris scale revealed a high degree of functional impairment of the HJ before THA in all the studied diseases. The average total score on the Harris scale before surgical treatment in AS was significantly higher than in RA and lower than in OA. According to the majority of parameters characterizing functional limitations in the HJ, AS patients had similar indices with RA patients.A high degree of structural and functional changes in the HJ before surgical treatment may potentially increase the risks of postoperative complications, whereas better results can be expected with initially higher functional capabilities.